(untitled) (University of Khartoum Engineering Journal, 2022)
The study of electromagnetic signals propagation through dusty media (dust storms, air with suspended dust particles), requires knowledge of some of the electrical and mechanical properties of that media. The aim of this paper is to describe the dusty media properties related to microwave signal propagation, and to give numerical values and statistics of these parameters for dust storms that frequently occur in Sudan. Most of these values and statistics were measured and investigated by the author over the last thirty years. The parameters which are considered in this paper include (1) the dust particles geometry which is approximated by an ellipsoid, and its orientation when suspended in air (2) the dust particles „particle size distribution‟; which is found to follow power law; (3) visibility statistics during dust storms as observed in some towns in Sudan, and its variation with high; (4) Permittivity and depolarization factor of the dusty medium, which is derived based on Maxwell Garnett formula and (5) dusty media Propagation Constant and Phase Shift, which are needed to estimate signal attenuation and cross depolarization.